2013
DOI: 10.1080/02664763.2013.868416
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate survival mixed models for genetic analysis of longevity traits

Abstract: A class of multivariate mixed survival models for continuous and discrete time with a complex covariance structure is introduced in a context of quantitative genetic applications. The methods introduced can be used in many applications in quantitative genetics although the discussion presented concentrates on longevity studies. The framework presented allows to combine models based on continuous time with models based on discrete time in a joint analysis. The continuous time models are approximations of the fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The possibilities to analyse multivariate mixed survival models for continuous and discrete time in a context of quantitative genetic applications were discussed by Maia et al . (). They found that the likelihood function of a continuous time model is typically much flatter than the likelihood function of a corresponding discrete time model.…”
Section: Resultsmentioning
confidence: 97%
“…The possibilities to analyse multivariate mixed survival models for continuous and discrete time in a context of quantitative genetic applications were discussed by Maia et al . (). They found that the likelihood function of a continuous time model is typically much flatter than the likelihood function of a corresponding discrete time model.…”
Section: Resultsmentioning
confidence: 97%
“…The deaths of hens that occurred in the time period from 30 weeks to 37 weeks of age (both extremes included) were studied using a discrete time proportional hazards model (DTPHM, see Kalbfleisch and Prentice 2002, Maia and others 2014a, b for technical details). This is a discrete-time version of the classic Cox proportional hazards model.…”
Section: Methodsmentioning
confidence: 99%
“…The inference was performed defining a suitable generalised linear mixed model as specified in Maia and others (2014a, b). Hypotheses tests on fixed effects were performed by applying parametrical bootstrap tests on the likelihood ratio statistics (100,000 bootstrap samples).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this part of the variability should be represented in the residual variance; but this is not possible to occur if the residual variance is set to be constant (Breslow & Clayton ; Maia et al . ). Hence, the probit model was performed with the free dispersion parameter.…”
Section: Methodsmentioning
confidence: 99%